Capital Structure and Family Business Governance: Gender Representation as a Moderating Variable - Nainggolan, Tiurma; Martusa, Riki; Meythi, Meythi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study examines the relationship between capital structure and family business governance in 81 family companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, with gender representation a moderating variable. The data were analyzed using pooled OLS regression with robust standard errors and 1%–99% winsorizing. The results show that capital structure has a negative effect on company performance. Long-term debt significantly reduces ROA and Tobin's Q because it increases financial risk. Short-term debt  and total debt are also predominantly negative, especially on Tobin's Q. These findings support the trade-off theory amid post-pandemic economic volatility. Gender representation does not moderate the relationship between capital structure and ROA. However, in Tobin's Q, the interaction of GR with LTD, STD, and TD is negative and significant. This indicates that higher GR strengthens the negative effect of debt on market value, due to the risk-averse nature of diverse boards, despite improving investor perceptions of governance. The study concludes that capital structure is detrimental to the governance of family businesses in Indonesia, and GR does not strengthen the positive relationship as hypothesized. Suggestions for further research include adding control variables, panel data models, and cross-country comparisons within ASEAN.